Comparison of clinical features and prognosis between ultrashort-segment and short-segment hirschsprung disease - Xie, Chuanping; Yan, Jiayu; Guo, Jianlin; Liu, Yakun; Chen, Yajun (Frontiers in Pediatrics, 2023)
Objective: To compare the differences in clinical features, postoperative complications, and long-term bowel function outcomes of ultrashort-segment Hirschsprung disease (USHD) and short-segment Hirschsprung disease (SHD). Methods: A retrospective study was conducted to compare patients with USHD or SHD who underwent transanal endorectal pull-through (TEPT) at Beijing Children’s Hospital between January 2014 and June 2021. Clinical details were collected from medical records. A long-term bowel function questionnaire (age＞4 years old) was completed by patient’s parents. Results: A total of 84 patients (USHD=15, SHD=69) were included. Age at diagnosis and radical surgery in the USHD group were significantly older than the SHD group (46 [38, 66] vs 34 [6, 55] months, p=0.002; 51 [39, 68] vs 37 [10, 68] months, p=0.001, respectively). Compared with SHD group, patients with USHD are more likely to suffer anastomosis leakage and postoperative enterocolitis after TEPT ([3/15, 33.3%] vs [1/69, 1.4%], p=0.017; [5/15, 33.3%] vs [6/69, 8.7%], p=0.023, respectively). In addition, patients in the USHD group are inclined to suffer lower bowel function scores (12.0 [7.5, 18.3] vs 17 [15, 19], p=0.018). Further, we found that patients in the USHD group were more likely to suffer poorer ability to hold back defecation (p=0.023), soiling (p=0.011), fecal accidents (p=0.004), and social problems (p=0.004). Conclusion: Compared with SHD, USHD is diagnosed and performed TEPT at an older age. In addition, patients with USHD are inclined to suffer postoperative enterocolitis, anastomosis leakage, and poorer long-term bowel function following TEPT.